Case report: Congenital hyperinsulinemia with ABCC8 gene mutations - Zhang, Jin; Wang, Jiyang; Chen, Hui (Frontiers in Pediatrics, 2022)
Background Congenital hyperinsulinemia (CHI) is an inherited disease of abnormal insulin secretion and is the main cause of persistent and intractable hypoglycemia in infants. The aim of this case report was to investigate the genetic mechanisms and treatment of CHI in an affected patient. Case summary We collected clinical data from, and performed gene capture, high-throughput gene sequencing analysis, and Sanger sequencing validation, in a child with CHI and his family to identify the causative gene mutations. Two heterozygous pathogenic mutations in the ATP-binding cassette subfamily C member 8 (ABCC8) gene were detected in the child: c.863G>A (p.Trp288Ter) in exon 6 and c.2506C>T (p.Arg836Ter) in exon 21. Sanger sequencing showed that c.863G>A was inherited from heterozygous mutations in the paternal line and c.2506C>T from heterozygous mutations in the maternal line. Conclusion The child was a CHI with a biallelic recessive heterozygous mutations in ABCC8 resulting in impairment of its encoded ATP-sensitive potassium (KATP) channel, poor response to diazoxide treatment, and developed diabetes after subtotal pancreatectomy.